A new laager for a “new” South Africa : Afrikaans film and the imagined boundaries of Afrikanerdom - Steyn, Adriaan Stefanus (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.